Pierre robin sendromlu bir hastada modifiye beslenme plağı ile dil konumunun düzeltilmesine bağlı olarak solunumun düzenlenmesi: Olgu sunumu - Akpınar, Sema; Oktay, Hüsamettin; Erdem, Abdülvahit (Aves Press Ltd, 2010)
Bu vaka raporunda PRS'lu bir bebek hastanın glossopitozisimn konservatif bir yöntemle tedavisi ve hastanın palatoplastiye hazırlanması sunulmaktadır.

In this case report, glossoptosis treatment of a newborn with PRS and her preparation tor palatoplasty with a conservative method is presented.
Management of respiration by arranging tongue position with a modified feeding plate on a pierre robin syndrome patient: Case report
Keywords: Pierre Robin Sendromu; Ortodontik Plak; Solunum; Pierre Robin Syndrome; Arranging Tongue Position; Respiration